Methods and outcomes of screening for pancreatic adenocarcinoma in high-risk individuals - Capurso, Gabriele (World J Gastrointest Endosc, 2015)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal neoplasia, for which secondary prevention (i.e., screening) is advisable for high-risk individuals with “familiar pancreatic cancer” and with other specific genetic syndromes (Peutz-Jeghers, p16, BRCA2, PALB and mismatch repair gene mutation carriers). There is limited evidence regarding the accuracy of screening tests, their acceptability, costs and availability, and agreement on whom to treat. Successful target of screening are small resectable PDAC, intraductal papillary mucinous neoplasms with high-grade dysplasia and advanced pancreatic intraepithelial neoplasia. Both magnetic resonance imaging (MRI) and endoscopic ultrasound (EUS) are employed for screening, and the overall yield for pre-malignant or malignant pancreatic lesions is of about 20% with EUS and 14% with MRI/magnetic resonance colangiopancreatography. EUS performs better for solid and MRI for cystic lesions. However, only 2% of these detected lesions can be considered a successful target, and there are insufficient data demonstrating that resection of benign or low grade lesions improves survival. Many patients in the published studies therefore seemed to have received an overtreatment by undergoing surgery. It is crucial to better stratify the risk of malignancy individually, and to better define optimal screening intervals and methods either with computerized tools or molecular biomarkers, possibly in large multicentre studies. At the moment, screening should be carefully performed within research protocols at experienced centres, offering involved individuals medical and psychological advice.